Impulsive noise reduction through OFDM-based PLC using a new adaptive recursive noise compensator. (2018) - Himeur, Yassine; Boukabou, Abdelkrim
Recently, powerline networks are increasingly employed for broadband data transmission such as internet, image and video delivery. Enhancing the quality of broadband transmission over powerline communication (PLC) channel is of utmost importance, which is an area of current interests. In this paper, we introduce the novel detection and noise reduction methods for PLC systems in impulsive noise environments. To reach this goal, a new adaptive recursive noise compensator (ARNC) algorithm is proposed. It is based on the iterative detection and estimation of the impulsive noise using the signal to impulsive noise power ratio (SINR), and the peak to average power ratio (PAPR) in the time domain after channel equalisation and demodulation. In fact, a new cliping/blanking function is introduced to estimate and detect the impulsive bursts. By evaluating the bit error rate (BER) and mean square error (MSE), the proposed technique illustrates high performance in an attenuated 15-paths condition.